If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -10c + -1 = 4 + -4c Reorder the terms: 6 + -1 + -10c = 4 + -4c Combine like terms: 6 + -1 = 5 5 + -10c = 4 + -4c Solving 5 + -10c = 4 + -4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4c' to each side of the equation. 5 + -10c + 4c = 4 + -4c + 4c Combine like terms: -10c + 4c = -6c 5 + -6c = 4 + -4c + 4c Combine like terms: -4c + 4c = 0 5 + -6c = 4 + 0 5 + -6c = 4 Add '-5' to each side of the equation. 5 + -5 + -6c = 4 + -5 Combine like terms: 5 + -5 = 0 0 + -6c = 4 + -5 -6c = 4 + -5 Combine like terms: 4 + -5 = -1 -6c = -1 Divide each side by '-6'. c = 0.1666666667 Simplifying c = 0.1666666667
| -12=4u+4 | | 2(v+1)=3v+23 | | 3(x+5)+6=-6 | | 1/3x^2-10x | | -2a+7=-23 | | 3(y+4)-2y=2(y+1) | | (2x+4)9=(3x-30)9 | | 2(v+1)=3u+23 | | x=3x+6x-9 | | x^3-6x^2-20x+120=0 | | 4t+3m=1529 | | log^3=1 | | -2-5b+8b=-8(-3-6b)-5(8+6b) | | 6(-2)-y=-18 | | 6y=49-y | | 2a+a=39 | | 7w=w+18 | | -7v+6=-36 | | 6(3)-y=-18 | | 2.4=02 | | a+1-2a-1E+1=2 | | y=3x+6x-9 | | 8x-15y=0 | | a+b-(ab)=1 | | 6(2)-y=-18 | | ba=a+b+1 | | 3(c+3)+8=-10 | | 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 |